1998
DOI: 10.1159/000029972
|View full text |Cite
|
Sign up to set email alerts
|

Growth-Regulative Activity of Human Alpha-Fetoprotein for Different Types of Tumor and Normal Cells

Abstract: The dose-dependent α-fetoprotein (AFP) reactivity of different types of tumor cells and normal embryonal fibroblasts, which are capable of taking up AFP, was investigated. High doses (more than 100 µg/ml) of purified human AFP were shown to induce strongly dose-dependent growth inhibition of human hepatoma HepG2 cells, human lymphoblastoma MT4 cells, lymphoma Jurkat cells and murine fibroblastoma L929 cells. Human mammary carcinoma MCF-7 cells also revealed a growth inhibitory response to AFP, although to a le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
73
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 41 publications
1
73
0
Order By: Relevance
“…This suggestion is in agreement with recent observations that AFP can act as a growth regulator under certain circumstances. Increased proliferation in vitro in response to AFP has been observed for developing or embryonic cells, 15,18 mouse and human hepatoma cells, 17 but not the untransformed cells because of the absence of specific membrane AFP receptors. 45 The AFP-enhanced proliferation could be diminished by anti-AFP antibody.…”
Section: Discussionmentioning
confidence: 99%
“…This suggestion is in agreement with recent observations that AFP can act as a growth regulator under certain circumstances. Increased proliferation in vitro in response to AFP has been observed for developing or embryonic cells, 15,18 mouse and human hepatoma cells, 17 but not the untransformed cells because of the absence of specific membrane AFP receptors. 45 The AFP-enhanced proliferation could be diminished by anti-AFP antibody.…”
Section: Discussionmentioning
confidence: 99%
“…When treated with AFP, the two oncogenes in Bel 7402 cells express promptly, thereafter the expression of these oncogenes dramatically declines. Previous researches had showed that AFP promoted the proliferation [1][2][3][4][5][6] and some oncogene expression of many tumor cells [15,16] . Cell growth was regulated by various factors, in which, some oncogene coding proteins have an important function in modulating growth and differentiation of the cells.…”
Section: Discussionmentioning
confidence: 99%
“…AFP always accompanies with the growth of liver cells, and it is possible that AFP may be related to the proliferation of tumor or fetal cells. Some investigations had showed that AFP could be individually synergy with other growth factors to promote the growth of many tumor or normal cells [1][2][3][4][5][6] . Alpha-fetoprotein (MW 69 ku) is a kind of biomacromolecules, and it is impossible to directly permeate the cells to regulate cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…4 AFP is a growth-regulating hormone with the capacity to stimulate or inhibit growth. 5 From fertilization through birth, AFP holds an important physiological role as a developmental promoter for the fetus. More recent reports have shown that AFP has antiestrogenic activity and can inhibit the growth of estrogen dependent cancer.…”
Section: Introductionmentioning
confidence: 99%